Biocultural determinants of overweight-obesity among adult women experiencing the nutritional transition in the Democratic Republic of Congo - Wakilongo, Wakenge; Abbeddou, Souheila; Vanhoutte, Lucie; Amougou, Norbert; Mubagwa, Muko; Elmira, Clémence; Pasquet, Patrick; Cohen, Emmanuel (Frontiers in Nutrition, 2024)
The African Great Lakes region is experiencing rapid urbanization process which leads to a nutritional transition and its related chronic diseases. Like other Great Lakes countries, the nutritional transition in the Democratic Republic of Congo (DRC) is reflected by increased non-communicable diseases, including morbid obesity. The 2014 Demographic Health Survey (DHS) reported an increasing prevalence of overweight among women, from 10% in 2001 to 16% in 2014, with over 20% of people in several provinces of the DRC classified as overweight-obese. This study aimed to determine the prevalence as well as the main biocultural determinants of overweight-obesity among adult women in the DRC. In a cross-sectional survey including a representative sample of adult Congolese women living in the South Kivu province, participants were randomly recruited using a two-stage cluster sampling, after an initial urban-rural stratification. The sample size calculation was based on previous results from DHS. Thus, 495 individuals were selected, including 325 urban and 170 rural subjects. Data were collected from households by dietitians who were specifically trained for this survey. In this study population, the prevalence of overweight-obesity was 33.6%, with 7.1% classified as obese. This prevalence was significantly higher among urban people, while all subjects with obesity were from the older age group (>35y). Using binomial logistic regressions, we observed that overweight-obesity was significantly positively associated with the length of urban residence, i.e. Migrants’ status: “New residents” 4.6 [1.9–11.7] p<0.003, “Long term residents” 8.7 [3.5–21.5] p<0.001; Socio-economic status (SES): “High” 2.4 [1.1–5.3] p<0.03 and Stoutness valorization: “Yes” 6.1 [3.4–10.9] p<0.001. In a pathway analysis based on a structural equation model (SEM), we found that urban residence and SES increased overweight-obesity through a positive association with processed food consumption and a negative association with physical activity. Age increased overweight-obesity through a negative association with physical activity, while stoutness valorization increased overweight-obesity directly. Public authorities in the DRC should consider the main findings of this original study identifying how socio-demographic and socio-ecological factors participate jointly in the rising prevalence of overweight-obesity in the country, to properly guide public health policies, especially in at-risk subgroups.